Coronavirus disease 2019: an overview - Prahalad, Ajna; Soti, Varun (International Journal Of Community Medicine And Public Health, 2021)
Coronavirus disease 2019 (COVID-19) has caused over four million deaths worldwide and continues to affect millions across the globe. This review aims to provide an overview of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the progress made to counter COVID-19 through therapeutics and immunizations. We searched preclinical and clinical COVID-19 literature published between January 2018 through June 2021 on PubMed. The medical subject headings used in the literature search were COVID-19, SARS-CoV-2, Treatment, Remdesivir, Cytokine Storm, Hydroxychloroquine, Epidemiology, Angiotensin-Converting Enzyme 2 Receptor, Vaccines, and Mitigation. There is credible evidence that shows that the spike protein in the SARS-CoV-2’s structure is crucial for the host to be infected. It spreads through different modes, primarily through aerosols and carriers. Pathophysiologically, SARS-CoV-2 triggers a cytokine storm leading to systemic inflammation, which can be fatal. Although treatment with Remdesivir and Dexamethasone and massive vaccinations have significantly reduced the mortality rate, COVID-19 remains a significant threat. The emergence of SARS-CoV-2’s different strains, notably the Delta variant, demonstrates that the COVID-19 pandemic is not over. More vaccine distribution and increased efforts in developing anti-SARS-CoV-2 drugs, social distancing, masking, and practicing good hygiene will be crucial in defeating COVID-19.